Immediate and Long-term Results of Stenting of the Unprotected Left Coronary Artery Trunk in Patients with Stable Coronary Heart Disease - G. K. Arutyunyan; S. I. Provatorov; N. S. Zhukova; A. S. Tereshchenko; D. V. Ognerubov; I. V. Emel’yanov; I. V. Krasnoshchekov; A. N. Samko (Вестник рентгенологии и радиологии, 2019)
Objective. To assess the immediate and long-term results of stenting of the unprotected left coronary artery (LCA) trunk in patients, by using different types of drug-eluting stents.Material and methods. The follow-up covered 282 patients who had undergone stenting of the unprotected LCA trunk. The mean follow-up was 34.6 [33.9; 35.3] months. The patients were divided into groups according to the type of a first-, second-, and third-generation implanted stent.Results. The incidence of adverse cardiovascular events in the patients of Group 1 was significantly higher than in those in Groups 2 and 3 (29 and 7.6%, p<0.0001). The incidence of thrombosis of first-generation stents (7.0%) was significantly higher than that of second- and third-generation ones (1.6%) (p=0.02). The incidence of adverse cardiovascular events was comparable between Groups 2 and 3, despite a shorter duration of dual antiplatelet therapy in the third-generation stent group. The absence of stent postdilatation in the LCA trunk is an independent risk factor for adverse prognosis.Conclusion. The use of second- and third-generation stents along with changes in the technical aspects of stenting of the unprotected LCA trunk leads to a substantial reduction in the risk of adverse cardiovascular events and allows the indications for intervention to be expanded in this patient category.